Extracellular Vesicles and the Inflammasome: An Intricate Network Sustaining Chemoresistance - Mezzasoma, Letizia; Bellezza, Ilaria; Romani, Rita; Talesa, Vincenzo Nicola (Frontiers in Oncology, 2022)
Extracellular vesicles (EVs) are membrane enclosed spherical particles devoted to intercellular communication. Cancer-derived EVs are deeply involved in tumor microenvironment remodeling, modifying the inflammatory phenotype of cancerous and non-cancerous residing cells. Inflammation plays a pivotal role in initiation, development, and progression of many types of malignancies. The key feature of cancer-related inflammation is the production of cytokines that incessantly modify of the surrounding environment. Interleukin-1β (IL-1β) is one of the most powerful cytokines, influencing all the initiation-to-progression stages of many types of cancers and represents an emerging critical contributor to chemoresistance. IL-1β production strictly depends on the activation of inflammasome, a cytoplasmic molecular platform sensing exogenous and endogenous danger signals. It has been recently shown that tumor-derived EVs can activate the inflammasome cascade and IL-1β production in tumor microenvironment-residing cells. Since inflammasome dysregulation has been established as crucial regulator in inflammation-associated tumorigenesis and chemoresistance, is conceivable that the use of inflammasome-inhibiting drugs may be employed as adjuvant chemotherapy to counteract chemoresistance. This review focuses on the role of cancer-derived EVs in tuning tumor microenvironment unveiling the intricate network between inflammasome and chemoresistance.